Eco luxury fashion and conscience - Ecologia, Tierra; Fakler, Merit; Contemporary Arts Media (Firm) (Melbourne, Vic. : Contemporary Arts Media, 2008)
Examines the environmentally sustainable fashion label Eco Logika, which specializes in combining fashion and conscience by using natural and environmentally friendly textiles. Discusses these textiles, including natural fibers, botanical dyes, eco yarns, sustainable silks, certified organic merino wool, certified organic cotton/hemp, environmentally friendly linen, recycled remnants, and recycled denim. Provides insights into designer Charlene O'Brien's artistic philosophy and shows examples of her work.
camera & directing, Merit Fakler ; produced by Tierra Ecologia.
Keywords: Clothing trade -- Environmental aspects; Fashion; Textile fibers